Diabetic Control Predicts Surgical Site Infection Risk in Orthopaedic Trauma Patients. Issue 10 (October 2019) - Reich, Michael S.; Fernandez, Isaac; Mishra, Abhinav; Kafchinski, Lisa; Adler, Adam; Nguyen, Mai P.
Abstract : Objectives: (1) To determine the incidence of surgical site infections (SSIs) in diabetic orthopaedic trauma patients and (2) to establish a protocol for managing diabetes mellitus (DM) in orthopaedic trauma patients. Design: Retrospective cohort study. Setting: Level 1 Trauma Center. Patients: All diabetic orthopaedic trauma patients who underwent surgical intervention with at least 1 month follow-up. Patients were classified as poorly controlled or controlled diabetic patients based on admission hemoglobin A1c and blood glucose (BG) levels. Interventions: Orthopaedic surgical intervention in accordance with fracture type and a standardized diabetes management protocol with internal medicine comanagement. Main Outcome Measurement: SSI incidence. Results: There were 260 patients during the study period. Two hundred two (77.7%) were included in the final analysis. Seventy-five (37.1%) patients met the criteria for poorly controlled DM. The overall rate of SSI was 20.8%; 32.0% for poorly controlled diabetic patients, and 14.2% for controlled diabetic patients ( P < 0.01). The admission blood glucose level (BG, P = 0.05), but not discharge BG, was associated with SSI incidence. Conclusions: Trauma patients with poorly controlled DM have a higher rate of SSIs than patients with controlled DM. Perioperative diabetes control does not seem to decrease infection rates in these patients. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.